The best method for evaluating anteversion of the acetabular component after total hip arthroplasty on plain radiographs - Yang Soo Park; Won Chul Shin; Sang Min Lee; Sang Ho Kwak; Jung Yun Bae; Kuen Tak Suh (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Several radiological methods for measuring the anteversion of the acetabular component after total hip arthroplasty (THA) exist, and no single standardized method has been established. We evaluated the reliability and accuracy of six widely utilized methods (Liaw et al., Lewinnek et al., Widmer, Hassan et al., Ackland et al., and Woo and Morrey) for measuring anteversion on plain radiographs, using a reference standard in the same definition obtained from the PolyWare programme. Methods We reviewed 71 patients who underwent primary unilateral THA. The anteversion of the acetabular component was measured on pelvis AP radiographs using five different methods (Liaw et al., Lewinnek et al., Widmer, Hassan et al., and Ackland et al.) and on cross-table lateral radiographs using the method of Woo and Morrey. The values obtained using the PolyWare programme, which determines the anteversion of the acetabular component by edge detection, were regarded as the reference standard. Results Intra- and inter-observer reliabilities were excellent for all methods using plain radiographs, including the PolyWare programme. The method of Liaw et al. obtained values similar to those obtained using the PolyWare programme and was thus considered accurate (P = 0.447). However, values obtained using the other five methods significantly differed from those obtained using the PolyWare programme and were thus considered less accurate (P < 0.001, P < 0.001, P < 0.001, P = 0.007, and P < 0.001, respectively). Conclusion The method of Liaw et al. is more accurate than other methods using plain radiographs for the measurement of the anteversion of the acetabular component after THA, with reference to the anteversion obtained from the PolyWare programme.